A decrease in tricuspid regurgitation pressure gradient during follow-up in patients with heart failure. (25th November 2020) - Seko, Y; Kato, T; Yamamoto, E; Yaku, H; Morimoto, T; Inuzuka, Y; Tamaki, Y; Ozasa, N; Yoshikawa, Y; Nagao, K; Kawase, Y; Kuwahara, K; et al.
Abstract: Objective: This study aimed to investigate the prognostic impact of the decrease in tricuspid regurgitation pressure gradient (TRPG) at 6-month follow-up in patients after discharge with heart failure (HF). Background: No previous study has reported the association between TRPG decrease during follow-up and clinical outcomes in HF. Methods: Among 748 patients with 6-months follow-up echocardiography after discharge from the acute decompensated heart failure in 19 centers in Japan, we analyzed 721 patients with available TRPG data and divided into two groups: the decrease in TRPG group (N=179) and no decrease in TRPG group (N=542). We defined the decrease in TRPG as >10mmHg decrease compared in the initial hospitalization. The primary outcome measure was a composite of all cause deaths and hospitalization due to HF. Results: The patients in the decrease in TRPG group had a lower prevalence of hypertension, dyslipidemia, atrial fibrillation, and a reduced EF, higher levels of blood albumin and lower levels of sodium than those in no decrease in TRPG group. The median follow-up duration after the follow up echocardiography was 302 (inter quartile range: 206–490), with a 90.9% follow up rate at 6-month. The cumulative 6-month incidence of the primary outcome measure was significantly lower in the decrease in TRPG group than in no decrease in TRPG group (12.2% vs. 18.9%, P=0.0011). After adjusting confounders, the excess risk of the decrease in TRPG relative to no decrease in TRPG for the primary outcome measure remained significant (HR: 0.60, 95% CI 0.34–0.99). There were no significant interactions between the subgroup factors and the effect of the decrease in TRPG for primary outcomes. Conclusions: HF patients with the decrease in TRPG at 6-month after discharge had a lower risk of clinical outcome than those without decrease in TRPG. Funding Acknowledgement: Type of funding source: None